Pelatihan dan Pendampingan Pengelolaan Data-Data Berbasis Teknologi Menuju Desa Mandiri Data - Sulistya Umie Ruhmana Sari; Mukti, Taufiq Satria; Safitri, Puspa Miladin Nuraida (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
Effective data management is essential for policymakers, particularly in Torongrejo Village, where data collected from citizens is processed to assess village potential and inform decision-making. Currently, the data management practices in Torongrejo Village remain primarily manual and have not fully embraced available data processing technologies. An initial survey revealed that many village operators require guidance in utilizing these technologies for efficient data management. This service activity aims to address this gap by providing training and support to empower the village apparatus in managing technology-based data, ultimately striving towards a self-sufficient data management system. Implementing this initiative involves several stages: identifying initial problems, socializing the activity, planning, executing the training, and monitoring the outcomes. The training's effectiveness was evaluated through questionnaires assessing participants' understanding of technology-based data management. The results indicate a significant improvement in the village apparatus's comprehension of data management techniques before and after the training, highlighting the importance of technological integration in enhancing local governance.